2012
DOI: 10.1007/s12039-012-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial studies of new N,N′-[5,5′-{2,2′-(bis-alkoxy) bis(2,1-phenylene)]bis(4-acetyl-4,5-dihydro-1,3,4-thiadiazole-5, 2-diyl)]diacetamide

Abstract: The bisthiadiazolines 4a(a-f) and 4b(a-f) built around the various rigid chains have been synthesized in good yields by refluxing bisthiosemicarbazones 3a(a-f) and 3b(a-f) in acetic anhydride medium. The reaction of bisaldehydes 2a(a-f) and 2b(a-f) with thiosemicarbazide under alcoholic medium yielded 3a(a-f) and 3b(a-f) and the former were obtained from the reaction of 2/4-hydroxybenzaldehyde with suitable alkylating agent in the presence of anhydrous K 2 CO 3 /dry acetone and Bu 4 N + I − (PTC). The intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Literature survey reported that compounds having 1,4‐bis(methoxymethyl) linkage are biologically active …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature survey reported that compounds having 1,4‐bis(methoxymethyl) linkage are biologically active …”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of bis‐thiosemicarbazone derivative 3 , which contains 1,4‐bis(methoxymethyl) linkage toward various hydrazonoyl halides in the presence of triethylamine as a basic catalyst was explored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2′-(4,4′-(1,4-Phenylenebis(methylene))bis(oxy)bis(4,1-phenylene)) bis(methan-1-yl-1-ylidene)bis(hydrazinecarbothioamide) 22c.Yellow solid, (66% yield), mp. 260-262°C, (Lit [49]…”
mentioning
confidence: 99%